2022
DOI: 10.3390/cancers14030700
|View full text |Cite
|
Sign up to set email alerts
|

Radiomic Phenotypes for Improving Early Prediction of Survival in Stage III Non-Small Cell Lung Cancer Adenocarcinoma after Chemoradiation

Abstract: We evaluate radiomic phenotypes derived from CT scans as early predictors of overall survival (OS) after chemoradiation in stage III primary lung adenocarcinoma. We retrospectively analyzed 110 thoracic CT scans acquired between April 2012−October 2018. Patients received a median radiation dose of 66.6 Gy at 1.8 Gy/fraction delivered with proton (55.5%) and photon (44.5%) beam treatment, as well as concurrent chemotherapy (89%) with carboplatin-based (55.5%) and cisplatin-based (36.4%) doublets. A total of 56 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…It is similar for older studies ( 29 , 30 ). Finally, two studies ( 31 , 32 ) have concluded to an improvement of prognostic with radiomics compared to conventional data on special patients. Moreover, the high prognosis value of stage in our study, at least equal to that of some RFs, must be emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…It is similar for older studies ( 29 , 30 ). Finally, two studies ( 31 , 32 ) have concluded to an improvement of prognostic with radiomics compared to conventional data on special patients. Moreover, the high prognosis value of stage in our study, at least equal to that of some RFs, must be emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics and clinical decision-supporting AI are emerging as the next frontier for diagnostic and prognostic medical imaging in the new era of precision medicine 2 . The aim of these tools is to automatically extract quantitative information from medical images for assisting evidence-based clinical decision-making [4][5][6]8 . However, several major challenges hamper the widespread clinical translation of these promising new capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…However, several major challenges hamper the widespread clinical translation of these promising new capabilities. The problem of data variability , which stems from differences in image acquisition and reconstruction settings among medical institutions, and scanner models, is recognized by many as a critical hurdle that requires dedicated solutions to enable the scalability of developed algorithms [6][7][8] . While recent studies made significant progress with solutions to account for some of the data variability, i.e., normalizations of image quality or imaging features, there is a critical need for lifelike phantoms that will enable the affirmations of these solutions without introducing additional risk to patients or logistical restrictions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach showed superiority as compared to conventional diagnostic methods, thereby putting forth a tool that may aid radiologists for early breast cancer detection in regular clinical practice settings [ 2 ]. Moreover, a team led by Dr. Kontos at the University of Pennsylvania extracted and analyzed retrospectively the radiomic phenotypes from 110 CTs of lung adenocarcinoma patients and showed that integration with clinical data significantly improved the prediction of overall survival in stage III non-small-cell lung cancer (NSCLC) after chemoradiation [ 3 ]. Interestingly, the same group demonstrated that the readers’ level of training and clinical experience (e.g., data scientist, medical student, radiology trainee, or specialty-trained radiologist) does not influence the ability to extract accurate radiomic features for NSCLC on CT, suggesting that the method is user-friendly and can be reliably applied by a variety of health care professionals [ 4 ].…”
mentioning
confidence: 99%